Pengaruh Brand Ambassador BTS dan Brand Trust terhadap Brand Image Tokopedia : Survei pada Masyarakat Pemgguna Marketplace Tokopedia di Kabupaten Ciamis - Izhar Yudiest Sebastian; Kusuma Agdhi Wardana; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was conducted in Ciamis Regency. This study was conducted with the aim of knowing the effect of Brand ambassadors and Brand trust on the Tokopedia Brand Image in the people of Ciamis Regency. The research method used is a survey method with a quantitative approach. The population used in this study are Tokopedia users who are domiciled in Ciamis. The sampling technique used is probability sampling with a simple random sampling approach, the number of samples used is 96 Tokopedia users with the condition that they have made a purchase transaction at least three times in the last six months. The data obtained in this study used primary data and secondary data. The data obtained from the research results were then processed using the classical assumption test, statistical analysis test, and hypothesis testing with the help of SPSS 25. Based on the correlation analysis test the Brand ambassador has a strong influence on the Tokopedia Brand Image with a correlation value of 0.644, while the Brand ambassador trust has a very strong influence on Tokopedia's Brand Image with a correlation value of 0.844. Based on the results of the F test, it shows that Brand ambassadors and Brand trust simultaneously have a significant effect on Tokopedia's Brand Image. The T test results show that Brand ambassadors partially have no significant effect on Tokopedia's Brand Image, while Brand trust partially has a significant effect on Tokopedia's Brand Image.